Casa de J. Maurín at Bonanza, with memorial tablet and photo. R. Fernandez i Jurado standing aside of the speaker de Godas. Biographical dates of de Godas on back
Casa de J. Maurín at Bonanza, with memorial tablet and photo. R. Fernandez i Jurado standing aside of the speaker de Godas. Biographical dates of de Godas on back.